Study Protocol: Role of Intermittent Fasting on Disease Severity and Quality of Life in Psoriasis and Psoriatic Arthritis: A Single-Blind Parallel Group Randomized Control Trial - Gray, Ashley; Rose, Lucy; Jolley, Dana; Bubic, Bianka; Korman, Abraham; Dulmage, Brittany; Sopkovich, Jennifer; Bechtel, Mark; Kaffenberger, Jessica; Kaffenberger, Benjamin H. (Academic Dermatology, 2023)
BACKGROUND Psoriasis and psoriatic arthritis (PsA) have a strong association with obesity and metabolic syndrome. Despite patient interest in non-pharmacologic methods to treat psoriasis and manage overall health, there is insufficient data available to guide dietary counseling. OBJECTIVE This study aims to identify the role of a popular anti-inflammatory diet known as intermittent fasting (IF) in psoriasis and psoriatic arthritis (PsA). METHODS A single-blind parallel group randomized control trial will be performed in 60 patients who have been diagnosed with psoriasis or PsA. Patients will be assigned 1:1 to either the IF group or control group. Patients assigned to the IF group will follow a 16:8 fasting IF method for the first 12 weeks, followed by the resumption of their routine diet. Patients assigned to the control group will follow their routine diet for 24 weeks. RESULTS A total of 24 patients have been enrolled in our study, with a final enrollment goal of 60 patients. The final visit is foreseen for July 2023. CONCLUSIONS This study aims to identify the role of a popular anti-inflammatory diet known as intermittent fasting (IF) in the management of psoriasis and PsA. Publishing this data will allow all dermatologists and the National Psoriasis Foundation to provide a consistent, evidence-based recommendation for IF as a potential non-pharmacologic intervention for patients with psoriasis and psoriatic arthritis (PsA).